(3OjhGf GHf GdeYJRs - (3YHO Gddg Hf eMeO GdeYJR HGddg Hf GdeJhcd Hf GdeYJUe Hf GdQTjO GdYHGSj, GHf GdeYJR, CHh GdYHGS,J (B296 (3g` s ((3eSYhO Hf YHGS Hf Ydj Hf CHj YeQh s)
(3ChdgG (B:s
(3bGd CHhGdYHGS aj GdaNQ Ydi bGajI GdCda(B: (3hSGQjI dG Jed GdHcG LQi OeYgG aj NOhO GdKQi s
(3BNQgG (B:s
(3CdG jG faS Ef JQVj HbhJ aCfJ YRjRI CHOG ZfjI OYj Yfc GdeWGeY hGdCeGfj ace CefjI LdHJ efjI s
(3fSNI SGHYIs
(3hgj oeNJGQGJ ef GdOjhGf LeY hGNJjGQ GdUGMH Hf YHGOs
(3hQO CjVkG JMJ Qbe (B2180(3, (B2191s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs